2001
DOI: 10.1063/1.1343518
|View full text |Cite
|
Sign up to set email alerts
|

Study of copper silicide retardation effects on copper diffusion in silicon

Abstract: A B-buried layer with a dose of 1×1014 atoms/cm2 was introduced into p-doped Si at a depth of 2.2 μm to enhance copper diffusion via its inherent gettering effect. Copper was then introduced into silicon either via a low-energy implantation followed by a thermal anneal, or through the thermal drive in of physical vapor deposited (PVD) copper film. Secondary ion mass spectrometry depth profiling of both annealed samples later indicated that while substantial amounts of copper was gettered by the B layer in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…It is reported that copper precipitates homogeneously forming copper silicides Cu 3 Si, which are positively charged with electroneutrality level at approximately E c Ϫ 0.2 eV. 20,22 Therefore, we measured the time constant with such a low intensity that the electron Fermi level was well below the electroneutrality level of copper silicides (E c Ϫ E fn ϭ 0.23 eV). We observed that the time constant was considerably higher, around 39000 s, which indicates a very low copper precipitation rate.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that copper precipitates homogeneously forming copper silicides Cu 3 Si, which are positively charged with electroneutrality level at approximately E c Ϫ 0.2 eV. 20,22 Therefore, we measured the time constant with such a low intensity that the electron Fermi level was well below the electroneutrality level of copper silicides (E c Ϫ E fn ϭ 0.23 eV). We observed that the time constant was considerably higher, around 39000 s, which indicates a very low copper precipitation rate.…”
Section: Resultsmentioning
confidence: 99%
“…The Cu particles did not disappear because the solubility limit of Cu in Si was very low and a Cu silicide layer was formed at the Cu particle/Si interfaces to suppress diffusion of Cu atoms to the Si substrate. 27 Next, the CAFM results in Fig. 2 and 3 indicate that the leakage current flow is difficult at the Cu particles, while dark points corresponding to the leaky positions were randomly distributed over the entire scan area except at the Cu particles.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was reported that micro-oxygen might indeed improve the thermal stability and performance of the diffusion barriers, such as, TaeGe(O)eN [25], TaeSieNeO [26] and MnSiO 3 [27]. Moreover, indium tin oxide (ITO), Ta 2 O 5 and TiO 2 all demonstrated good diffusion barrier candidates [28,29]. It is widely accepted that the thickness of the diffusion barrier rather than the resistivity play a critical role in the continuous downscale ULSI.…”
Section: Introductionmentioning
confidence: 99%
“…However, the inter-diffusion and reaction between Cu thin films and the dielectric layers limit the reliability of Cu interconnects and become the crucial issue in the field of microelectronics [4,5]. Therefore, an effective barrier layer is essential to block the unwanted atomic diffusion between Cu thin films and the dielectric layers.…”
Section: Introductionmentioning
confidence: 99%